Promosi Kebudayaan oleh Duta Kebudayaan Kota Palembang dalam Memperkuat Identitas Lokal - Saputra, Afridho; Yenrizal; Ningsih, Chairunnisah Putri Ayu (Edutik : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
This study aims to determine the forms of cultural promotion carried out by the Cultural Ambassadors of Palembang City and their implications for strengthening the local identity of the community. The study uses a qualitative descriptive method with data collection techniques through in-depth interviews, observation, and documentation. Informants consisted of officials from the Palembang City Culture Office, members of the Cultural Ambassadors (Cek Bagus and Cek Ayu), and cultural actors involved in cultural promotion activities. The results of the study show that cultural promotion is carried out through two main forms, namely promotion based on socio-cultural activities and promotion based on digital media. Direct promotion is carried out through festivals, exhibitions, and educational activities, while digital promotion utilizes social media as a means of disseminating cultural values to the wider community. These activities contribute positively to increasing public awareness and pride in local culture, as well as strengthening the image of Palembang City as a city with a cultural identity. However, its implementation still faces obstacles in the form of budget constraints, lack of institutional support, low community participation, and limited digital capabilities of cultural ambassadors. Therefore, increased cross-sector support and digital communication training are needed to make cultural promotion strategies more effective and sustainable in strengthening Palembang's local identity.